Pierse, Mary (ed.), George Moore: Artistic Visions and Literary Worlds. - Grene, Nicholas (ABEI Journal, 2007)
Pierse, Mary (ed.), George Moore: Artistic Visions and Literary Worlds. Newcastle: Cambridge Scholars Press, 2006, xvii + 246 pp.